Plug and Play Modular Façade Construction System for Renovation for Residential Buildings - Jorge Torres; Roberto Garay-Martinez; Xabat Oregi; J. Ignacio Torrens-Galdiz; Amaia Uriarte-Arrien; Alessandro Pracucci; Oscar Casadei; Sara Magnani; Noemi Arroyo; Angel M. Cea (Buildings, 2021)
The present paper focuses on the architectural and constructional features required to ensure that building envelope renovation are safe, functional, and adaptable to the building stock, with particular focus on “plug and play” modular facade construction systems. It presents the design of one such system and how it addresses these issues. The outcome of early-stage functional test with a full-scale mock-up system, as well as its applicability to a real construction project is presented. It is found crucial to obtain high quality information about the status of the existing façade with the use of modern technologies such as topographic surveys or 3D scans and point cloud. Detailed design processes are required to ensure the compatibility of manufacture and installation tolerances, along with anchor systems that deliver flexibility for adjustment, and construction processes adapting standard installation methods to the architectural particularities of each case that may hinder its use or require some modification in each situation. This prefabricated plug and play modular system has been tested by reproducing the holistic methodology and new technologies in the market by means of real demonstrators. When compared to more conventional construction methods, this system achieves savings in a real case of 50% (time), 30% (materials) and 25% (waste), thus achieving significant economic savings.